"Position Of The International Law From The Phenomenon Of Transgender People" (Journal of Namibian Studies : History Politics Culture, 2024)
This study tackled the position of the contemporary international law from the phenomenon that became of concern in most states, and it is the phenomenon of transgender people and the extent of availability of rights for them in verdicts of the International Laws. As well as the nature of the sexual transformation in International Law, and the rights of transgender people under the conventions, in three sections: the first topic dealt with the nature of transgender individuals, and the second topic focused on international legal trends in gender transformation, while the third topic was devoted to the rights of transgender people in international law. The judiciary in its approval of sex correction operations or not, as the prevailing trend authorized them with the presence of some contrary decisions. This study recommended that the international community should organise some conferences and seminars in order to clarify the concept of transgender people, as well as to clarify the religious opinion of the main religions in this category.